Reversible Pulmonary Arterial Hypertension Associated with Interferon-Beta Treatment for Multiple Sclerosis. Issue 5 (2015) - Gibbons, E; Promislow, S; Davies, RA; Chandy, G; Stewart, DJ; Contreras-Dominguez, V; Pugliese, C; Dunne, R; Mielniczuk, LM
Abstract : Interferon (IFN) therapy has an important role in the treatment of multiple sclerosis and chronic hepatitis C infection. A few case reports have described an association between IFN therapy and the development of irreversible pulmonary arterial hypertension (PAH), and it is currently listed as a possible drug-induced cause of PAH in the most recent classification of pulmonary hypertension. A causal link between IFN use and PAH remains to be elucidated; many reports of PAH resulting from IFN occur in individuals with some other risk factor for PAH. The authors present a case involving a patient with multiple sclerosis with no known risk factors for PAH, who developed severe PAH after exposure to IFN therapy. The patient experienced significant clinical and hemodynamic improvement, with normalization of her pulmonary pressures after the initiation of combination therapy for PAH. At 28 months after diagnosis, she remains asymptomatic with no hemodynamic evidence of PAH and has been off all PAH therapy for 10 months.